(untitled) (Revista de Medicina Clinica, 2021)
The sleep-wake process represents one of the basic needs of human beings, as well as feeding and reproducing; however, sociocultural changes have modified our sleep habits in some way, triggering some sleep disorders. Advances in sleep-wake cycle research have made it easier to understand the different alterations that develop due to inadequate sleep hygiene in people. It should be noted that many of the investigations in this regard are based on studies of lower mammals, under the knowledge that the sleep-wake cycle is similar in mammals, thereby transferring this knowledge to human beings with their limitations. Understanding the basic neurophysiology of sleep does not facilitate understanding the different sleep disorders that are manifested in the people who come to our medical consultation.